The Influence of Transformational Leadership, Quality of Human Resources, and Discipline toward Community Satisfaction at the Office of Dinas Kependudukan and Pencatatan Sipil Kota Kupang - Melianus Imanuel Manalor; Luis Marnisah; Jefirstson Richset Riwukore (Enrichment : Journal of Management, 2022)
The purpose of this study is specifically to obtain the results of the analysis of the relationship betwen the variables of transformational leadership, the quality of human resources, and the discipline of civil servants on the level of community satisfaction partially and simultaneously. The research method uses a descriptive and verification survey. Collecting data use questionnaires and documentation techniques. This research is an associative research, where in there are variables related and they can influence other variables. The population of this research is employees who work in the Dinas Kependudukan and Pencatatan Sipil Kota Kupang as many as 78 people and 240 people from Kupang City community. Data analysis using analyzing tools of SPSS 23. Testing of the data uses t test, that transformational leadership has an effect on community satisfaction with t count of 5,536 < t table of 1,96, quality of human resources has an effect on the community satisfaction with t count of 33,683 < t table of 1,96, discipline of civil servants has an effect on the community satisfaction with t caount of 20,817 < t table of 1,96. Simultaneously, transformational leadership, quality of human resources, and discipline of the state civil servants influence on community satisfaction with F count of 459,956 > F table of 2,633. The result of this study shows that transformational leadership, quality of human resources, and discipline of the state civil servants has an effect positively and significantly toward community at the Dinas Kependudukan and Pencatatan Sipil Kota Kupang.